Recent progress in miRNA biogenesis and decay - Xavier Bofill-De Ros; Ulf Andersson Vang Ørom (RNA Biology)
MicroRNAs are a class of small regulatory RNAs that mediate regulation of protein synthesis by recognizing sequence elements in mRNAs. MicroRNAs are processed through a series of steps starting from transcription and primary processing in the nucleus to precursor processing and mature function in the cytoplasm. It is also in the cytoplasm where levels of mature microRNAs can be modulated through decay mechanisms. Here, we review the recent progress in the lifetime of a microRNA at all steps required for maintaining their homoeostasis. The increasing knowledge about microRNA regulation upholds great promise as therapeutic targets.